New information on the potency of sponge-associated actinobacteria as producer of plant growth-promoting bioactive compounds - Dwi Retnowati; Solihin, Dedy Duryadi; Ghulamahdi, Munif; Lestari, Yulin (Penerbit Universiti Kebangsaan Malaysia, 2018)
Sponge-associated actinobacteria are known as bioactive compounds producers with various biological functions, but their potency as plant growth promoters is rarely reported. This research aimed to investigate the potency of sponge-associated actinobacteria as plant growth promoters. Sponges used in these study were Callyspongia sp., Callyspongia aerizusa, Carteriospongia contorta, Chelanoplysilla sp., and Diacarnus bismarckensis. A total of 53 isolates have been isolated from that sponges by serial dilution method. All isolates classified into two groups, including non-Streptomyces and Streptomyces based on their morphological characters. Screening of sponge-associated actinobacteria isolates showed from 53 isolates there are 47 isolates produced indole acetic acid (IAA), 33 isolates inhibited the growth of Xanthomonas oryzae, 29 isolates grew on free N medium, 22 isolates produced HCN, eleven isolates inhibited the growth of Pyricularia oryzae, and five isolates had the capacity to solubilize phosphate. The results suggested that sponge-associated actinobacteria have the potency as plant growth promoter candidates and might be as biofertilizer on tidal lands.